(untitled) (Darya Ganj, New Delhi, 2001)
Contents of material: Library preservation. Preservation in automated libraries. Cataloguing technologies. Information storage and preservation. Library records and serials systems. Physical dimensions of preservation.
Keywords: Collection management ( Libraries ),Acquisitions (Libraries),Library technical services